MERANCANG PROSEDUR SELEKSI KARYAWAN PERUSAHAAN KONSULTAN TEKOLOGI INFORMASI - Meita Santi Budiani (Jurnal Psikologi Teori dan Terapan, 2010)
This article is focusing on Human Resources problems at PT. IF.  Companys human resource seems hard to achieve their personal targets. Besides that, the amount of companys employee is not enough to support company in achieving its sales target. For this reason, PT. IF needs to have a specific form in selection process in order to have good human resources. The results are 1). Human resources problem can be  fixed by making the right form of selection process; 2). The Selection Process is consist of psychological aspects and criteria quotition, predictor and interview guide quotition, and the selection stages which include curiculum vitae selection, psychological evaluation, dan interviews; 3). PT. IF  needs to have preparation and planning before conduct a selection processes, getting updated information can be good example. There are few problems that writer had found during the making of this research, the problems is in the time arrangement between writer and the job holder.